Pengelolaan Citra Profesional Ajudan Gubernur Jawa Barat: Studi Kasus Ajudan Milenial Gubernur Jawa Barat pada Program Jabar Future Leaders - Ahsania Fitri Dhamayanti; Nova Yuliati (UNISBA Press, 2023)
Abstract. The Governor of West Java has its own innovation in choosing his professional image adjutants, namely through the Jabar Future Leaders program which is a selection process for the best young adjutnt with an age range of 17-25 years from all provinces in Indonesia. The purpose of this study was to find out: 1) Governor of West Java’s Milenial Adjutant front stages condition, 2) How the Adjutant of Milenial Governor of West Java showed his professional attitude. West Java builds communication skills in carrying out their duties. The method used in this research is a qualitative method with a Case Study approach and Erving Goffman's Dramaturgy theory. The informants in this study were representatives of the selected Milenial Adjutant from batches 1-4 of the Jabar Future Leaders program. Data collection techniques used in this study were observation, in-depth interviews, documentation and literature study. The results in this study are that there are differences in the back stage and front stage of Millennial Adjutants to the Governor of West Java, to have a professional image in the realm of the front stage, millennial adjutants must make preparations and evaluations. The results of this study are to form a professional front stage, adjutants make preparations before assignment and evaluation after assignment. Keywords: Adjutant, Front stage, Back Stage, Image, Professional, Dramaturgy Abstrak. Gubernur Jawa Barat memiliki inovasi tersendiri dalam memilih ajudannya yang cakap dan memiliki citra profesional, yakni melalui program Jabar Future Leaders yang merupakan proses seleksi ajudan muda terbaik dengan rentang usia 17-25 tahun dari seluruh provinsi di Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui: 1) Bagaimana keadaan front stage Ajudan Milenial Gubernur Jawa Barat, 2) Bagaimana sikap profesional yang ditunjukkan oleh Ajudan Milenial Gubernur Jawa Barat. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan Studi Kasus serta menggunakan teori Dramaturgi Erving Goffman. Informan dalam penelitian ini adalah perwakilan Ajudan Milenial terpilih dari batch 1-4 program Jabar Future Leaders. Tenik pengumpulan data yang dilakukan dalam penelitian ini adalah observasi, wawancara mendalam, dokumentasi, dan studi pustaka. Hasil dalam penelitian ini adalah untuk membentuk front stage yang professional, ajudan melakukan persiapan sebelum bertugas dan evaluasi setelah bertugas. Kata Kunci: Ajudan, Front stage, Back Stage, Citra, Profesional, Dramaturgi